1998
DOI: 10.1038/sj.onc.1202135
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of Met-HGF/SF during Ras-mediated tumorigenesis/metastasis

Abstract: Aberrations in Met-hepatocyte growth factor/scatter factor (HGF/SF) signaling have been implicated in the acquisition of tumorigenic and metastatic phenotypes. Here we show that murine NIH3T3 and C127 cells transformed by the Ras oncogene overexpress the Met receptor, resulting in enhanced HGF/SF-mediated responses in vitro including invasion through basement membrane. Accompanying the increase in Met in rastransformed NIH3T3 cells, there is a decrease in endogenous HGF/SF expression as previously observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 15 publications
2
59
0
2
Order By: Relevance
“…This HGF/SF-independent regulation of Met expression likely occurs through transcriptional activation via an AP-1 response element in the Met promoter. 35,60,68,69 In contrast, the HGF/SF dependent regulation of Met protein expression, on stimulation with exogenously added HGF/SF, is likely regulated by Met degradation via the ubiquitinylation pathway. 60 It is presently not known whether the amount of expressed Met receptor determines the responsiveness of benign or malignant prostate epithelial cells to HGF/SF stimulation in vivo.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This HGF/SF-independent regulation of Met expression likely occurs through transcriptional activation via an AP-1 response element in the Met promoter. 35,60,68,69 In contrast, the HGF/SF dependent regulation of Met protein expression, on stimulation with exogenously added HGF/SF, is likely regulated by Met degradation via the ubiquitinylation pathway. 60 It is presently not known whether the amount of expressed Met receptor determines the responsiveness of benign or malignant prostate epithelial cells to HGF/SF stimulation in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…As previously demonstrated, autocrine secretion of HGF/SF promotes metastases in a mouse model of tumor metastasis and HGF/SF plays a role in Ras-mediated metastases formation. 28,30,33,35 HGF/SF is an important mediator of stromal-epithelial interactions in the normal prostate; however, its specific function on Met-expressing epithelial cells has not been fully defined. 36 HGF/SF biological activity in the conditioned medium of mouse prostatic stromal cells, immortalized human myofibroblastic prostate stromal cells (PrSC), and primary PrSC stimulated the scattering, motility, and collagen gel invasion of DU145 prostate cancer cells and the proliferation of mouse prostate epithelial cells (PrEC).…”
mentioning
confidence: 99%
“…Tumor cell migration can be influenced by HGF and its receptor, Met. In Webb and coworkers' study (133), HGF and Met receptor signaling was associated with a transformed phenotype in rastransformed NIH 3T3 cells. Furthermore, the HGF pathway was recently reported to affect the adhesion and invasion of cancer cells (134).…”
Section: Growth Factor Receptor Pathways and Osteopontinmentioning
confidence: 99%
“…We found that a locus (7q21) containing the MET gene was amplified in part of these EGFR wild-type tumors and immunohistochemically validated overexpression of MET protein in these tumors. MET was shown to be implicated in ras-mediated tumorigenicity (44,45) and activated in many tumors (34 -36). Although the number of cases with MET amplification is small in this study, it is tempting to speculate that amplification of the MET gene may play a role similar to EGFR mutation in lung adenocarcinoma.…”
Section: Imaging Diagnosis Prognosismentioning
confidence: 99%